Budgeting in Hungary - Kraan, Dirk-Jan (OECD Publishing, 2007)
This review of the Hungarian budget process was carried out in May 2006. The review covers budget formulation, budget execution, parliamentary approval, accounting and auditing, and sub-national financing. Hungary has modernised its budget process over the last ten years, first as part of the pre-accession programme and then, since EU accession in 2004, in connection with the Convergence Programme 2005-08. Nevertheless, there remain some shortcomings which include the focus on the actual (non-cyclically adjusted) deficit, the focus on the budget year rather than the medium term, the lack of rules of budgetary discipline, and the lack of transparency concerning forecasts and outcomes. Hungary's long-term growth record and general economic outlook are good, but institutional reform to correct these shortcomings is important for fiscal consolidation and macroeconomic stability